Q-Switched Fiber Laser With A Tungsten Disulfide Saturable Absorber Prepared By The Drop Casting Method - Razak, Nurul Nadia; Yasin, Moh; Zakaria, Zahriladha; Abdul Latiff, Anas; Harun, Sulaiman Wadi (Photonics Society Of Poland, 2017)
We experimentally demonstrate a passively Q-switched erbium-doped fiber laser (EDFL) operation by using a saturable absorber (SA) based on tungsten disulfide (WS2). By depositing a WS2 thin film layer at the end of an optical fiber ferrule, we fabricated an SA device. The SA is incorporated into an Erbium-doped fiber laser (EDFL) cavity to generate a Q-switching pulses train operating at 1559.8 nm. As a result, stable passively Q-switched EDFL pulses with a maximum output pulse energy of 123.2nJ, repetition rate of 104.1kHz, and pulse width of 9.61μs are achieved when the input pump power is 142.1mW at a wavelength of 980nm.